Benefits from plant resistance in reducing reliance on fungicides in cereal disease management - Viljanen-Rollinson, S.L.H.; Marroni, M.V.; Butler, R.C. (New Zealand Plant Protection, 2010)
Two field trials autumn and springsown with seven fungicide treatments and three wheat cultivars with different levels of resistance to Puccinia striiformis the cause of stripe rust were carried out at Lincoln during the 20092010 growing season to assess the value of utilising disease resistance within an integrated wheat disease management strategy The development of stripe rust was monitored during the season The resistant cultivar CFR02452 was free of stripe rust in all treatments including the no fungicide treatment There was more disease in the autumnsown trial than in the springsown trial The moderately resistant cultivar Torlesse had less stripe rust than the susceptible cultivar Claire in both trials and negligible disease in the springsown trial In cultivar Claire for both trials two fungicide applications that started before disease was present provided disease control that was similar to four applications but fungicide applications that commenced once the disease had established provided little control of stripe rust